2010
DOI: 10.1080/15226510903051773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Matter Additions on Uptake of Weathered DDT byCucurbita pepossp.pepocv. Howden

Abstract: Greenhouse studies were conducted to assess the impact of organic matter additions on plant uptake of DDT [2,2-bis(chlorophenyl)-1,1,1-trichloroethane] from weathered soil. Cucurbita pepo ssp. pepo cv. Howden pumpkins were grown in 100 g of DDT contaminated soil ([DDT] - 1100 ng/g) mixed with equal volumes of either clean soil, perlite, vermiculite, peat, potting soil, or granular activated carbon (GAC) to give total organic carbon contents of 2.4%, 2.5%, 2.6%, 11.5%, 12.2%, and 27.3%, respectively. As in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Th erefore, AC amendment to PCB-contaminated sediments is a promising tool to immobilize remaining PCBs after maximal PCB remediation has been achieved.Terrestrial contaminated sites could potentially use a similar technology to trap residual POPs. In a preliminary study, Lunney and colleagues demonstrated that high concentrations of AC had the potential to inhibit DDT bioavailability in soils (Lunney et al, 2010). Th e addition of 50% AC to highly contaminated soils (v/v) prevented DDT bioaccumulation in pumpkins and zucchinis (Cucurbita pepo ssp pepo cv.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Th erefore, AC amendment to PCB-contaminated sediments is a promising tool to immobilize remaining PCBs after maximal PCB remediation has been achieved.Terrestrial contaminated sites could potentially use a similar technology to trap residual POPs. In a preliminary study, Lunney and colleagues demonstrated that high concentrations of AC had the potential to inhibit DDT bioavailability in soils (Lunney et al, 2010). Th e addition of 50% AC to highly contaminated soils (v/v) prevented DDT bioaccumulation in pumpkins and zucchinis (Cucurbita pepo ssp pepo cv.…”
mentioning
confidence: 99%
“…Th e addition of 50% AC to highly contaminated soils (v/v) prevented DDT bioaccumulation in pumpkins and zucchinis (Cucurbita pepo ssp pepo cv. Howden) (Lunney et al, 2010).…”
mentioning
confidence: 99%
“…The specific cultivar selected for the field experiment, C. pepo cv. Howden, is a known accumulator of ΣDDX (Denyes et al 2016 ; Lunney et al 2010 , 2004 ; Paul et al 2015 ; White 2002 , 2001 ; Whitfield Åslund et al 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…The above discussion shows that microbes are highly specialized to facilitate nutrient availability for plant growth as well as their development [101]. They protect plants from pathogen attack by generating competition with pathogens.…”
Section: Rhizoremediation Processmentioning
confidence: 99%